Fault Impedance Characterization for High Voltage Applications in Power Systems - Swaminathan, Rangarajan (My University, 2024)
Abstract The thesis investigates the effects of the characteristics of high impedance faults on the performance of line distance protection. Two typical models are implemented.The verification of those models is done both with conventional sources and with a renewable source of Type-3 and Type-4 wind turbines. The results are compared with the standard PSCAD fault block model available in the software library. When modeling the conventional source and considering the time-varying characteristic of high-impedance fault, the difference is mainly observed in the fault detection time and the final impedance calculation by the relay. This is due to the time-variant and asymmetric nature of high Impedance Faults. The impact is that the fault detection time for high impedance faults is higher, e.g., 70 ms compared to the standard PSCAD fault block cases with a constant fault resistance whose fault detection time is 30 ms. Also, a simple compensation block for correcting the resistance is implemented and analysis is done. The renewable source study is done to understand why traditional fault calculation techniques cannot be applied due to the system behavior during the fault scenario. The time-variant behavior of high-impedance faults has been found to affect the fault detection time. The asymmetric behavior affects the final impedance calculated by the relay which could lead to the relay not detecting the fault.
Keywords: Keywords: High Impedance faults, distance protection